2010
DOI: 10.1007/s13199-010-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Sea-land transitions in isopods: pattern of symbiont distribution in two species of intertidal isopods Ligia pallasii and Ligia occidentalis in the Eastern Pacific

Abstract: Studies of microbial associations of intertidal isopods in the primitive genus Ligia (Oniscidea, Isopoda) can help our understanding of the formation of symbioses during sea-land transitions, as terrestrial Oniscidean isopods have previously been found to house symbionts in their hepatopancreas. Ligia pallasii and Ligia occidentalis co-occur in the high intertidal zone along the Eastern Pacific with a large zone of range overlap and both species showing patchy distributions. In 16S rRNA clone libraries mycopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…in their hepatopancreas ( Wang et al, 2007 ; Fraune and Zimmer, 2008 ). Similarly, Hepatoplasma (but not Hepatincola ) has been observed in two other intertidal species, Ligia occidentalis and L. pallasii ( Eberl, 2010 ). The evolutionary or phylogenetic relevance of this finding remains unclear.…”
Section: A Diverse Symbiont Assemblymentioning
confidence: 70%
See 1 more Smart Citation
“…in their hepatopancreas ( Wang et al, 2007 ; Fraune and Zimmer, 2008 ). Similarly, Hepatoplasma (but not Hepatincola ) has been observed in two other intertidal species, Ligia occidentalis and L. pallasii ( Eberl, 2010 ). The evolutionary or phylogenetic relevance of this finding remains unclear.…”
Section: A Diverse Symbiont Assemblymentioning
confidence: 70%
“…Early molecular studies of isopod microbiota focussed exclusively on digestive tissues, due to the interest in bacteria potentially involved in nutritional processes. Despite being based only on relatively small 16S rRNA gene clone libraries, this work already hinted at a high bacterial diversity: numerous taxa from the phyla Bacteroidetes, Firmicutes, and Proteobacteria (e.g., Bacillus, Bacteroides, Enterococcus, Pseudomonas ) have been observed in the hindgut of P. scaber ( Kostanjsek et al, 2002 , 2004a ; Lapanje et al, 2010 ) and diverse Proteobacteria ( Aeromonas, Burkholderia, Ralstonia, Rhodobacter, Vibrio ) in the midgut caeca of the freshwater isopod A. aquaticus ( Wang et al, 2007 ) and the semiterrestrial species L. pallasii and Ligia occidentalis ( Eberl, 2010 ). A recent in-depth pyrotag screening of the bacterial community in several tissues of A. vulgare from laboratory-reared lineages as well as populations sampled in the field ( Dittmer et al, 2016 ) provides us with the most detailed picture of the isopod microbiome to date.…”
Section: The Big Picture: the Terrestrial Isopod Microbiomementioning
confidence: 99%
“…Because isopods provide a stable shelter for microbes, isopod guts are often habitats of different symbionts. As cases in point, previous studies have described the presence of Mycoplasma and Rickettsiales bacteria in the hepatopancreas of isopods (Fraune and Zimmer, 2008;Eberl, 2010). However, the role of the mycoplasma symbionts remains ambiguous.…”
Section: Discussionmentioning
confidence: 93%
“…It is hypothesised that symbiotic relationships such as this may have facilitated the expansion of isopods to terrestrial environments as no such bacteria were found in the hepatopancreas of isopods from the marine environment [59]. An ESV representative of the "Candidatus Hepatoplasma" assignment, detected in lobster, was identical to that isolated from Norway lobster (Nephrops nervegicus) [45] and 96% identical to a clone isolated from the high intertidal/sublittoral isopod Ligia occidentalis [60].…”
Section: Discussionmentioning
confidence: 99%